1996
DOI: 10.1016/0925-4773(96)00521-7
|View full text |Cite
|
Sign up to set email alerts
|

Chick NKx-2.3 represents a novel family member of vertebrate homologues to the Drosophila homeo☐ gene tinman: differential expression of cNKx-2.3 and cNKx-2.5 during heart and gut development

Abstract: NKx homeodomain proteins are members of a growing family of vertebrate transcription factors with strong homology to the NK genes in Drosophila. Here, we describe the cloning of cNKx-2.3 and cNKx-2.5 cDNAs and their expression during chick development. Both genes are expressed in the developing heart with distinct but overlapping spatio-temporal patterns. While cNKx-2.5 is activated in early precardiac mesoderm and continues to be uniformly expressed throughout the mature heart, expression of NKx-2.3 starts la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…Nkx-2.5 RNA has previously been shown to be expressed in the embryonic chick heart up to the looped, tubular stage (HH 15-17) (Schultheiss et al, 1995;Buchberger et al, 1996). During later development, we found that a heterogeneous pattern of Nkx-2.5 expression emerged (Figs.…”
Section: Nkx-25 Mrna Is Significantly Elevated In the Central Conducsupporting
confidence: 53%
“…Nkx-2.5 RNA has previously been shown to be expressed in the embryonic chick heart up to the looped, tubular stage (HH 15-17) (Schultheiss et al, 1995;Buchberger et al, 1996). During later development, we found that a heterogeneous pattern of Nkx-2.5 expression emerged (Figs.…”
Section: Nkx-25 Mrna Is Significantly Elevated In the Central Conducsupporting
confidence: 53%
“…In vitro transcribed and translated proteins were generated by using TNTcoupled reticulocyte lysate systems (Promega). 1 l of reticulocyte lysate containing 35 S-labeled wild type or mutant Csx/Nkx2.5, Nkx2.3, or Nkx2.6/Tix protein was mixed with fusion proteins in a 400 l of binding buffer (20 mM HEPES, pH 7.5, 100 mM NaCl, 5 mM MgCl 2 , 0.1% Triton X-100, aprotinin (2 g/ml), pepstatin (0.7 g/ml), 0.1 mM PMSF, 1 mM DTT, and 1% bovine serum albumin) at 4°C for 2 h. Beads were washed with binding buffer (without bovine serum albumin) and subjected to SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…After extensive washing, the protein complexes were resolved on SDS-PAGE and visualized by autoradiography. Approximately 25% of input 35 S-labeled Csx/ Nkx2.5 protein associated with MBP-Csx/Nkx2.5 ( Fig. 2A, lane …”
Section: Csx/nkx25 Forms a Homodimer On A Palindromic Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Nkx2.5, the vertebrate homolog of the Drosophila tinman gene, is expressed in the cardiac lineage of fish, chick, and mouse (Chen and Fishman, 1996;Buchberger et al, 1996;Lints et al, 1993). It is essential for myogenic and morphogenetic differentiation in the mammalian heart (Lyons et al, 1995).…”
Section: Bmp4 Msx1 and Nkx25 Expression During Oft And Av Cushionsmentioning
confidence: 99%